Real‐time visualization of lung malignancy with needle‐based confocal laser endomicroscopy during shape‐sensing robotic‐assisted bronchoscopy - Fabiana Diaz‐Churion; Alejandra Yu Lee‐Mateus; David Abia‐Trujillo; Margaret M. Johnson; Andras Khoor; Neal M. Patel; Janani Reisenauer; Sebastian Fernandez‐Bussy (Respirology Case Reports, 2023)
Abstract Robotic‐assisted bronchoscopy (RAB) improves endoscopic diagnostic yield of solitary pulmonary nodules (SPN). Needle‐based confocal laser endomicroscopy (nCLE) is an emerging technology that allows high‐resolution, in‐vivo, real‐time assessment of living tissues at a cellular and subcellular level. Their combined use has been scarcely reported. We used them simultaneously in three patients with SPNs. For each, the nodule was evaluated with nCLE and sampled for pathology, followed by mediastinal staging. Median age was 77 years (67% male). Median nodule minimum size was 1.8 cm and maximum was 2.1 cm. nCLE detected abnormal patterns suggestive of malignancy for all nodules and pathology confirmed primary lung adenocarcinomas in two patients and lung primary squamous cell carcinoma in the other. The combined use of RAB with nCLE may potentially enhance the differentiation of malignant cells in real‐time and increase sample adequacy, accuracy, and diagnostic yield when biopsying a suspicious pulmonary lesion.